Angiograhic profile and in-hospital outcome of young patients presenting with ST Elevation Myocardial Infarction (STEMI) in tertiary cardiac hospital - Pandey, Rabindra; Maskey, Arun; Shrestha, Bishal; Budhathoki, Arjun; Malla, Sabindra Bhupal; Baniya, Bibek; Bhatta, Surendra; Shrestha, Sashit; Yadav, Parveen Kumar (Journal of Advances in Internal Medicine, 2021)
Objective: To assess the angiographic profile and in hospital outcomes of primary percutaneous coronary intervention among young patients presenting with acute ST Elevation Myocardial Infarction and underwent primary PCI.Methods: The retrospective observational study was conducted at Shahid Gangalal National Heart Centre (SGNHC), Kathmandu, from july 2020 to June 2021, and included acute ST-Elevation Myocardial Infarction patients underwent primary percutaneous coronary intervention (PCI). Data was collected on demographic, angiographic, and in-hospital outcomes. Patients